Bergson and Phenomenology
XII, 277 p. 1 illus.
Keywords: Examining the revival of Bergsonism for phenomenology, leading scholars of both areas inaugurate a dialogue long overdue. By assessing phenomenology's readings of Bergson and Bergsonian challenges to phenomenological methods, the essays in this volume explore anew the issues of central concern in contemporary continental philosophy.